The Tail That Wags the Economy: Beliefs and Persistent Stagnation - Kozlowski, Julian; Veldkamp, Laura; Venkateswaran, Venky (Journal of Political Economy, 2020)
The Great Recession was a deep downturn with long-lasting effects on credit, employment, and output. While narratives about its causes abound, the persistence of gross domestic product below precrisis trends remains puzzling. We propose a simple persistence mechanism that can be quantified and combined with existing models. Our key premise is that agents do not know the true distribution of shocks but use data to estimate it nonparametrically. Then, transitory events, especially extreme ones, generate persistent changes in beliefs and macro outcomes. Embedding this mechanism in a neoclassical model, we find that it endogenously generates persistent drops in economic activity after tail events.